Specialty income and career decision making: a qualitative study of medical student perceptions. Issue 6 (1st March 2019) - Phillips, Julie P; Wilbanks, Deana M; Rodriguez‐Salinas, Diana F; Doberneck, Diane M
Abstract : Context: Medical educators in the USA are interested in the ways medical students make career choices because shortages in key specialties, particularly primary care specialties, limit access to care. Although anticipated specialty income is a strong predictor of student interest, no studies have qualitatively explored the reasons why income is important to students. By better understanding students' perspectives on income and specialty choice, educators can help students make choices that fit their goals and better educate students about the specialties in which the need for expansion is greatest. Methods: In 2012, Year‐2 students at one USA medical school were invited to write an essay about how debt and anticipated income levels influence their career choices. A total of 132 essays (response rate: 67%) were qualitatively analysed using a hermeneutic phenomenology approach to conventional content analysis, in which themes emerge inductively from the data. Researchers employed peer debriefing, modified member checking, thick description, code–recode strategies, audit trails and reflexivity to ensure quality and rigour. Although this analysis initially focused on student perceptions of specialty income, prestige also emerged as an important related theme. Results: Three major findings emerged. Income is of varying importance to different students. Students value income because it provides freedom and flexibility, and power and security. Students recognise that high income confers social prestige. Students also define specialty prestige in other ways, including match competitiveness, perceived expertise, opportunities for advancement through fellowships, and power and autonomy. Conclusions: Medical students' perspectives of specialty income, specialty choice and prestige are more complex than previously reported. Medical educators should frame conversations about specialty choices in ways that incorporate varied perspectives on income and prestige. Health policymakers should recognise that income and prestige influence medical students' decisions in complex ways. These insights may inform strategies to counteract shortages in key specialties, including primary care specialties. Abstract : Income, why do we love thee? Students report that high income influences their career decisions in many ways by providing freedom, flexibility, power, security, and social prestige.